Devadatta adii sp. nov. (Odonata: Zygoptera: Devadattidae) from Upper Siang District, Arunachal Pradesh, India - Sawant, Dattaprasad; Joshi, Shantanu; Pawar, Ujwala; Naik, Pratiksha; Khan, Fahim; Nawge, Viraj; Kunte, Krushnamegh (Zootaxa, 2024)
We erect a new species Devadatta adii sp. nov. based on five males and five females collected from Upper Siang District, Arunachal Pradesh, India. The males of the new taxon are unique in terms of having a golden yellow lateral pterothorax, strongly curved cerci and filamentous genital ligula. We also provide illustrations of male thorax and caudal appendages of Devadatta spp..